Case Report: Prompt Response to Savolitinib in a Case of Advanced Gastric Cancer With Bone Marrow Invasion and MET Abnormalities - Ye, Wen; He, Liping; Su, Lei; Zheng, Zhousan; Ding, Meilin; Ye, Sheng (Frontiers in Oncology, 2022)
Gastric cancer is one of the most common malignant tumors and patients show a short survival, those combined with bone marrow invasion have a median survival of only 37 days. Here we reported the treatment of a 47-year-old male with advanced gastric cancer and complicated with bone marrow invasion and extensive metastases, who did not tolerate chemotherapy, under monotherapy with savolitinib, a MET receptor tyrosine kinase inhibitor. Before treatment, the patient was in severe pain and presented with thrombocytopenia and hemorrhagic anemia. Savolitinib was given based on amplification and rearrangement of the MET gene in his tumor. After savolitinib treatment, the patient's condition promptly improved, efficacy evaluation indicated partial remission, and the patient was alive and remained progression-free at 15 weeks at the time of reporting. No obvious adverse reactions occurred. Besides, another case of a female gastric cancer patient with MET amplification who received savolitinib monotherapy as a third-line treatment that remained progression-free at 12 weeks was also reported. This report provides a new reference for understanding MET abnormalities in gastric cancer and offers a possibility for future application of MET tyrosine kinase inhibitors in the therapy of gastric cancer with MET abnormalities. Also, it suggests that sequencing of MET can be considered a routine target in advanced gastric cancer patients.